Synergistic nanostructuring of CoNi-carbide/reduced graphene oxide derived from porous coordination polymers for high-performance hybrid supercapacitors - Aboelazm, Eslam Atef Abdelaziz; Khe, Chengseong; M.F., Shukur; Chong, Kwok Feng; Mohamed Shuaib, Mohamed Saheed; Hegazy, Mohamed Barakat Zakaria (Elsevier Ltd, 2023)
Porous coordination polymers (PCPs) and metal-organic frameworks (MOFs) have emerged as promising materials for nanostructuring inorganic functional materials with applications in energy storage. In this study, our aim was to synthesize CoNi-carbide (CoNi-C)/reduced graphene oxide (rGO) hybrids by annealing CoNi-cyanide bridged coordination polymers (CoNi-CP) under a nitrogen atmosphere. The resulting CoNi-C/rGO hybrids exhibited exceptional electrochemical performance, surpassing the individual components (CoNi-C and rGO). The hybrids demonstrated a specific capacitance of 1177 F g−1 and an electroactive surface area of 130.87 m2 g−1. By optimizing the CoNi-C/rGO ratio, we achieved the highest specific capacitance. Furthermore, we constructed a coin cell using CoNi-C/rGO-2 as the positive electrode and rGO as the negative electrode, which showed excellent performance with an energy density of 31.6 Wh kg−1 at a power density of 750 W kg−1 and capacitive retention of 84 % over 8000 charging cycles. Our findings provide valuable insights into designing and developing high-performance electrode materials for energy storage, with potential applications in various devices.